Spatial and Temporal Evolution Characteristics of Low Water Level Based on 70 years’ Measured Data: A Case Study of Dongting Lake in China - Ge, Hua; Zhu, Lingling; Long, Rui; Deng, Chunyan; Yin, Shuran; Zhang, Ouyang (Frontiers in Earth Science, 2022)
In recent years, the operation of cascade reservoirs in the upper reaches of Yangtze River led by the Three Gorges Reservoir has significantly changed the low water level of Dongting Lake, which has brought an adverse impact on the water resources and ecological security in the lake area. As a result, the low water level situation of Dongting Lake is attracting more and more attention. Based on the abundant and long-term daily observation data of Dongting Lake and main stream of Yangtze River, the spatial and temporal evolution characteristics of low water level in Dongting Lake area since 1950s were analyzed in this paper, especially during the storage period of the Three Gorges Reservoir. In addition, the influence of the jacking effect of the Yangtze River on Dongting Lake was also discussed to analyze the impact of the Three Gorges Reservoir. The results show that the annual minimum water level in Dongting Lake area over the years generally occurs from January to February and December. Since it is not within the storage period of the Three Gorges Reservoir, it is not affected by the Three Gorges Reservoir. However, the average water level in September and October during the main storage period of the Three Gorges Reservoir has been significantly reduced, and the closer it is to the main stream of the Yangtze River, the greater the influence is. In recent years, affected by the advance of the impounding period, the average water level has decreased further in September. In addition, the low water level of Dongting Lake is obviously affected by the jacking effect of the main stream of the Yangtze River. After the impoundment of the Three Gorges Reservoir, the water surface slope of Dongting Lake area has been decreased, while that of the main stream of the Yangtze River has been increased. This has strengthened the jacking effect of the main stream. The research results can provide reference for the solution of water resources and ecological crisis in Dongting Lake area.